Comparative study of perhydropolysilazane protective films. (2nd September 2022) - Shmagina, Elizaveta; Danilson, Mati; Mikli, Valdek; Bereznev, Sergei
ABSTRACT: Silicon dioxide thin films are a promising alternative to protective glass in solar cells. In this work, one-layer and four-layer thin films of a perhydropolysilazane (PHPS) were spin-coated from solution in dibutyl ether and cured by exposure to moderate temperatures or ultraviolet (UV) light to obtain glassy SiOx layers. Optical and morphological properties as well as their long-term stability were studied using XPS, FTIR, UV-Vis spectroscopy, and SEM microscopy with EDX analysis. The results showed that the process of converting PHPS layers to SiOx continues after the completion of the curing procedure for both methods. However, the composition of the thermally cured films is similar to silicon oxide, while the UV-cured samples demonstrate a composition similar to silicon dioxide due to differences in the reactions occurring during the curing process. The prolonged transformation process opens up possibilities for creating self-improving protective coatings based on PHPS. GRAPHICAL ABSTRACT: UF0001